2009
DOI: 10.1186/1476-4598-8-74
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of leptin receptor predicts an unfavorable outcome in Middle Eastern ovarian cancer

Abstract: Background: Recent epidemiological studies have suggested that obesity is associated with ovarian cancer. Obesity hormone leptin and its receptor (Ob-R) contribute to tumor development by enhancing cell growth and survival. This study was design to investigate the prevalence of leptin and Ob-R in Middle Eastern epithelial ovarian cancer (EOC) and to analyze the role of leptin and the mechanisms under its action in EOC tissue sample and cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 36 publications
8
99
0
3
Order By: Relevance
“…13 Diverse cancer cells derived from different tissues, such as brain, breast, colon or prostate, were reported to have ObR expression. [21][22][23][24][25] Furthermore, Ob-R overexpression not only correlated with the degree of malignancy, but also was an independent prognostic variable to predict poor progression-free survival in brain tumor, ovarian cancer, and breast cancer, 24,26,27 which suggested that ObR+ cells might be closely related with tumor initiation and development. In this study, we claimed that ObR+ glioblastoma cells presented chemoresistance, which showed that TMZ could not inhibit cell proliferation and could not induce apoptosis effectively.…”
Section: Discussionmentioning
confidence: 99%
“…13 Diverse cancer cells derived from different tissues, such as brain, breast, colon or prostate, were reported to have ObR expression. [21][22][23][24][25] Furthermore, Ob-R overexpression not only correlated with the degree of malignancy, but also was an independent prognostic variable to predict poor progression-free survival in brain tumor, ovarian cancer, and breast cancer, 24,26,27 which suggested that ObR+ cells might be closely related with tumor initiation and development. In this study, we claimed that ObR+ glioblastoma cells presented chemoresistance, which showed that TMZ could not inhibit cell proliferation and could not induce apoptosis effectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serum leptin levels are higher in patients diagnosed with endometrial and ovarian cancer compared to those observed in healthy individuals (14)(15)(16). Furthermore, in vitro studies on human cell lines of ovarian and endometrial cancer indicate that leptin leads to the activation of signaling pathways, such as JAK2̸STAT3, MAPK̸ERK and PI3K̸AKT, which stimulate cell proliferation and inhibit apoptosis (17,18), demonstrating its biological ability to promote the malignant behavior of cancers by stimulating growth, migration and invasiveness of tumor cells (19). Those effects are exerted via its binding to its protein receptor (Ob-R), which belongs to the class I cytokine receptor family (20).…”
Section: Introductionmentioning
confidence: 99%
“…14,23-25 p-AKT, BCL-XL, and XIAP were scored as described previously. 26,27 Statistical Analysis The JMP7 (SAS Institute, Cary, NC, USA) software package was used for data analyses. Survival curves were generated using the Kaplan-Meier method, with significance evaluated using the Mantel-Cox log-rank test.…”
Section: Immunohistochemistrymentioning
confidence: 99%